Application of Pulse Radiolysis to Mechanistic Investigations of Catalysis Relevant to Artificial Photosynthesis. Issue 22 (27th October 2017) - Grills, David C.; Polyansky, Dmitry E.; Fujita, Etsuko
Abstract: Taking inspiration from natural photosystems, the goal of artificial photosynthesis is to harness solar energy to convert abundant materials, such as CO2 and H2 O, into solar fuels. Catalysts are required to ensure that the necessary redox half‐reactions proceed in the most energy‐efficient manner. It is therefore critical to gain a detailed mechanistic understanding of these catalytic reactions to develop new and improved catalysts. Many of the key catalytic intermediates are short‐lived transient species, requiring time‐resolved spectroscopic techniques for their observation. The two main methods for rapidly generating such species on the sub‐microsecond timescale are laser flash photolysis and pulse radiolysis. These methods complement one another, and both provide important spectroscopic and kinetic information. However, pulse radiolysis proves to be superior in systems with significant spectroscopic overlap between the photosensitizer and other species present during the reaction. Herein, the pulse radiolysis technique and how it has been applied to mechanistic investigations of halfreactions relevant to artificial photosynthesis are reviewed. Abstract : Observing fleeting moments : Pulse radiolysis (PR) is a powerful technique for investigating redox transformations relevant to artificial photosynthesis, such as catalytic water oxidation and proton or CO2 reduction. The rapid generation of powerful reducing or oxidizing species coupled with time‐resolved spectroscopy in the UV/Vis to mid‐IR range allows the observation of transient intermediates that are often inaccessible through other techniques.